O18 Prevalence of malnutrition screening. (19th June 2022) - Willsmore, James; Poo, Stephanie; Wordsworth, Dominic; Long, Matthew; Ruban, Aruchuna
Abstract : Introduction: Malnutrition is common in hospitalised patients, and identifying and treating malnutrition early improves patient outcomes. 1 NICE Clinical Guideline 32 advocates screening of inpatients for malnutrition upon admission and thereafter at weekly intervals. 2 Assessment should include body mass index (BMI), percentage unintentional weight loss and should consider the time over which nutrient intake has been unintentionally reduced and/or the likelihood of future impaired nutrient intake. The Malnutrition Universal Screening Tool (MUST) may be used for these purposes 2 . Our aim was to assess screening for malnutrition in adults admitted to gastroenterology wards, auditing against these standards 2 . Methods: This was a retrospective study of adult inpatients admitted across three adult gastroenterology wards at a London NHS trust over a 30-day period between August and September 2021. Data was collected from electronic patient records, including demographics, documentation of nutritional data (weight, BMI, percentage unintentional weight loss and likelihood of future reduced nutrient intake, MUST score) and if the patient was referred to dietetics. Primary endpoints were proportion of inpatients with an admission MUST score and with a weekly MUST score, if length of stay was ≥ 7 days. Secondary endpoints were proportion of inpatients with a documented weight and percentage weight loss. Proportion of patients referred to dietetics was recorded. Numerical data are expressed as number ± standard deviation (range). Results: 188 patients (97 female, 91 male) were admitted during the study period. Mean age was 59.7 ± 17.3 (range 19 to 94) years. Mean length of stay was 13.5 ± 21.2 days. Of 288 patients, 110 (61.1%) patients had a length of stay ≥7 days. Of 188 patients, 156 (83.0%) had an admission MUST score. Of 110 patients with a length of stay ≥7 days, 30 (27.3%) had a weekly MUST score. Of 188 patients, 174 (92.6%) had a documented weight, 138 (76.7%) had a documented BMI and 139 (73.9%) had a documented percentage weight loss. 51 (27.1%) of inpatients were referred to dietetics. Conclusions: Malnutrition is common in hospitalised patients and our results suggest that improvements are required in identifying, screening and monitoring of nutritional status by weekly re-screening of inpatients and early referral to dietetics. Recommendations of this audit include providing education on malnutrition screening at the junior doctors' trust induction and implementing a weekly reminder function on the electronic notes to prompt nutritional re-assessment. References: Stratton Emma Beggs R, et al. National Survey of Malnutrition and Nutritional Care in Adults UK Malnutrition Awareness October 2020 . https://www.bapen.org.uk/pdfs/reports/mag/national-survey-of-malnutrition-and-nutritional-care-2020.pdf Nutrition Support for Adults: Oral Nutrition Support, Enteral Tube Feeding and Parenteral Nutrition Clinical Guideline ; 2006. www.nice.org.uk/guidance/cg32